Derivational Morphology on Calum Scott’s Song from Bridges Album: - Kusumawardhani, Paramita; Sihombing, Eklesia; Nuraeni, Cicih (Universitas Nasional, 2024)
This study aimed to know the derivational morphemes in Calum Scott Song from Bridge Album. Derivation is a part in linguistics. Linguistics is the scientific study of language. Derivational morpheme is part of morphology. Morphology means the smallest significant units of grammar. Morphology has two parts, there are derivational and inflectional. Derivational is related to affixes such prefixes, infixes, and suffixes, meanwhile inflectional is related to plural, possessive, progressive, pat time, comparative and superlative. Morphemes are divided into two parts, they are free morphemes and bound morphemes. Free morphemes are morphemes that can stand on their own, while bound morphemes that cannot stand with their own. This research focuses on derivational morphemes in Calum Scotts songs in the album Bridges. The songs in the album were used as the data of the research. This research used qualitative method and the result were some derivational morphemes found in the album Bridges. From 7 songs there are 4 prefix, such as re-, pre-, sur-, and a-, and some suffixes, such as -ent, -ion, -full, -ing, -ed, -ness, -less, -ly, -ment, -ian, -er, -y, -a.